Tunable pentapeptide self-assembled β-sheet hydrogels - Clarke, David E.; Parmenter, Christopher D. J.; Scherman, Oren A. (Wiley-VCH Verlag, 2018)
Oligopeptide-based supramolecular hydrogels hold promise in a range of applications. The gelation of these systems is hard to control with minor alterations in the peptide sequence significantly influencing the self-assembly process. This makes sequence design difficult whereby typical self-assembly rules cannot be applied. We explored the design of pentapeptide sequences with different charge distributions and discovered that they formed robust, pH-responsive hydrogels. Through altering the concentration and charge distribution of the peptide sequence, we demonstrated that the stiffness of the hydrogels can be tuned across two orders of magnitude (2-200 kPa). Also, through the reassembly of the b-sheet interactions, the hydrogels can both selfheal and shear thin. Using spectroscopic and cryo-imaging techniques, we investigated the relationship between peptide sequence, molecular structure and how these influence the mechanical properties of the hydrogel. These pentapetide hydrogels attributed with tunable morphology and mechanical properties have promise in tissue engineering, injectable delivery vectors and 3D printing applications.